Prediction of the Winner of the Mojokerto Regency Pilkada Through a Socio-Historical Religious Approach: Prediksi Pemenang Pilkada Kabupaten Mojokerto Melalui Pendekatan Sosiso History Religius - Khoiri; Hindarto (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to develop a prediction model for the winner of the Mojokerto Regency Regional Head Election (Pilkada) using a social history religious approach. This approach combines the analysis of community social data, political history, and religious factors that play a role in shaping voter behavior in the area. In this study, data were collected through interviews, surveys, and secondary data analysis that included past political trends, patterns of religious support, and the influence of religious institutions on the electoral process. By using quantitative and qualitative methods, this research aims to formulate significant factors in determining the winner of Pilkada and build a prediction model that can be used as a reference for prospective leaders and related parties in formulating a more effective campaign strategy. The results of this study are expected to provide new insights in understanding the dynamics of local politics, especially in Mojokerto Regency, and contribute to the development of election prediction methods based on a religious social history approach.